IMPROVEMENT OF A MINI-THERMAL POWER PLANT WITH A COLLECTOR AND AUTOMATION (Innovative Technologica: Methodical Research Journal, 2023)
It is developed the solar energy using equipment of low electrical energy producing without liquid vapouring. It is used the “solar following system” in the equipment.